The Doctor Blake mysteries. Season two [videorecording (DVD)] - McLachlan, Craig, 1965-; Garner, Nadine; Cousins, Charlie (BBC Worldwide Americas, Inc., 2015)
Doctor Lucien Blake returns to Ballarat after an attempt to reunite with his long lost daughter. But it's no longer the safe haven he left behind: Danny has been transferred to Melbourne, replaced by a new Senior Constable who seems hell bent on making Blake's job as police surgeon as difficult as possible. Blake's old nemesis Patrick Tyneman has called in the help of some powerful men to keep an eye on Blake. And of course there are the strange and baffling murders that come his way, there are mysteries seeping out of every corner - from political corridors and church vestries, to, art galleries and rock'n'roll halls.